Ultra-low noise spectral broadening of two combs in a single ANDi fiber - Sandro L. Camenzind; Benoît Sierro; Benjamin Willenberg; Alexander Nussbaum-Lapping; Anupamaa Rampur; Ursula Keller; Alexander M. Heidt; Christopher R. Phillips (APL Photonics)
Developing high-brightness, low-noise supercontinuum (SC) sources is critical for a variety of ultrafast photonics applications. A key challenge in achieving low-noise operation is the suppression of incoherent nonlinear effects and the associated noise amplification. All-normal dispersion (ANDi) SC sources exhibit considerably reduced noise levels compared to conventional soliton-based methods, but their previous lowest-noise demonstrations were limited by amplified spontaneous emission from amplified femtosecond pump laser systems, which seeds incoherent nonlinearities and degrades SC quality. Consequently, the ultimate low-noise limits of coherent SC generation have not been demonstrated by experimental results. Here, we report ultra-low noise, shot-noise-limited SC generation by directly driving the SC process with the un-amplified output of a high-power dual-comb Yb:CALGO oscillator centered at 1053 nm. The resulting SC combs each have a spectrum spanning 820–1280 nm (−20 dB), 1.6 W average power, 1.03 GHz repetition rate, and a comb-line power of ≈10 μW. We conduct detailed noise studies of the SC by analyzing various ≈15-nm-wide spectral bands. All bands reach a shot-noise-limited relative intensity noise below −160 dBc/Hz at 100-kHz to few-MHz noise frequencies. Furthermore, the central spectral bands exhibit an unprecedented noise suppression of the pump laser’s technical noise above ≈2 kHz by >20 dB, which agrees with our semiclassical simulations. Finally, we simultaneously couple both combs into a single ANDi fiber to generate a dual-comb SC with highly symmetric spectra and correlated noise properties between the combs. Coherently averaged linear optical sampling measurements on the dual-comb SC exhibit a high signal-to-noise ratio, showcasing its potential for real-time spectroscopic measurements.